COMPARISON OF TWO BIOMODELS (BALB/C MICE AND SPRAGUE DAWLEY RATS) IN THE ALKALINE COMET ASSAY - Arencibia Arrebola, Daniel Francisco; Rosario Fernández, Luis Alfredo; Suárez Fernández, Yolanda Emilia; Vidal Novoa, Alexis (BIOCYT Biología Ciencia y Tecnología, 2020)
This article had as objective to carry out a comparison between Balb/c mice and Sprague Dawley rats as biomodel in the alkaline comet assay, keeping in mind the basal frequency and that induced with Cyclophosphamide, the induction of single strand breaks (SSB) or alkali-labile sites formation on DNA of peripheral blood leukocytes. Ten animal/sex/species/group of Balb/c mice and Sprague Dawley rats were used, and treated for 14 days. Using a negative control group (not treated), two substance-vehicle controls and a positive control received cyclophosphamide 50 mg/kg, via intraperitoneal. After two weeks the alkaline electrophoresis gel was performed for individual cells from leukocytes of peripheral blood to screen for possible DNA damage. The best biomodel in both sexes was the SD rats differing significantly with the results obtained in Balb/c mice keeping in mind the spontaneous and induced values of DNA damage. This study shows SD rats are a more efficient model for preclinical genotoxic evaluation of drugs, vaccines and natural products.